Management of malignant colon polyps: Current status and controversies - Aarons, Cary B (World J Gastroenterol, 2014)
Colon cancer remains a significant clinical problem worldwide and in the United States it is the third most common cancer diagnosed in men and women. It is generally accepted that most malignant neoplasms of the colon arise from precursor adenomatous polyps. This stepwise progression of normal epithelium to carcinoma, often with intervening dysplasia, occurs as a result of multiple sequential, genetic mutations-some are inherited while others are acquired. Malignant polyps are defined by the presence of cancer cells invading through the muscularis mucosa into the underlying submucosa (T1). They can appear benign endoscopically but the presence of malignant invasion histologically poses a difficult and often controversial clinical scenario. Emphasis should be initially focused on the endoscopic assessment of these lesions. Suitable polyps should be resected en-bloc, if possible, to facilitate thorough evaluation by pathology. In these cases, proper attention must be given to the risks of residual cancer in the bowel wall or in the surrounding lymph nodes. If resection is not feasible endoscopically, then these patients should be referred for surgical resection. This review will discuss the important prognostic features of malignant polyps that will most profoundly affect this risk profile. Additionally, we will discuss effective strategies for their overall management.